2015
DOI: 10.1177/1933719115585146
|View full text |Cite
|
Sign up to set email alerts
|

Higher SOD1 Gene Expression in Cumulus Cells From Infertile Women With Moderate and Severe Endometriosis

Abstract: It is questioned whether worsening of oocyte quality and oxidative stress (OS) are involved in the pathogenesis of infertility related to endometriosis and in compromised intracytoplasmic sperm injection (ICSI) outcomes. Cumulus cells (CCs) protect oocytes from entering apoptosis induced by OS. Thus, we carried out a case-control study comparing expression of superoxide dismutase 1 (SOD1), superoxide dismutase 2 (SOD2), and glutathione peroxidase 4 (GPX4; genes encoding for the main antioxidant enzymes) in CCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 54 publications
0
24
0
3
Order By: Relevance
“…Higher expression of NOS can cause LH to stimulate the proliferation of CCs48. Recent research showed higher SOD1 gene expression in CCs in infertile women, which could be a biomarker of clinical pregnancy after Intra-Cytoplasmic Sperm Injection (ICSI)49. Expression of the PLA2G4A gene is regulated by LH/hCG-dependent induction in granular cells via the adenylyl cyclase/cAMP pathway; therefore, lower expression of PLA2G4A in PCOS CCs reflected an abnormal LH surge50.…”
Section: Discussionmentioning
confidence: 99%
“…Higher expression of NOS can cause LH to stimulate the proliferation of CCs48. Recent research showed higher SOD1 gene expression in CCs in infertile women, which could be a biomarker of clinical pregnancy after Intra-Cytoplasmic Sperm Injection (ICSI)49. Expression of the PLA2G4A gene is regulated by LH/hCG-dependent induction in granular cells via the adenylyl cyclase/cAMP pathway; therefore, lower expression of PLA2G4A in PCOS CCs reflected an abnormal LH surge50.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies also report that women with endometriosis have high levels of oxidative stress markers and low levels of antioxidant markers in serum (Lambrinoudaki et al, 2009;Prieto et al, 2012) and follicular fluid (Singh et al, 2013;Nasiri et al, 2017), suggesting increased oxidative stress in these patients (Nakagawa et al, 2016). Recently, altered oxidative stress in the follicular fluid of women with endometriosis was proposed to have a negative impact in folliculogenesis, affecting apoptosis, damaging DNA in GCs and cumulus cells (Goud et al, 2014;Donabela et al, 2015), and potentially altering oocyte development. Accordingly, follicular fluid from women with endometriosis, when applied to bovine and murine oocytes, promotes meiotic abnormalities such as chromosomic instability and spindle abnormalities (Choi et al, 2007;Mansour et al, 2010;Da Broi et al, 2014), implying a connection between oxidative stress and cell cycle.…”
mentioning
confidence: 99%
“…Sample size calculation was analyzed according to the previous study by Donabela et al [13] with mean of SOD1 relative gene expression in healthy women control group; 2.06 2 -Δ ΔCT (SD = 0.53). To compare two different means, the sample size calculation was performed with the following expectation; SOD1 gene expression level in POR was lower than NOR by 20%, resulting in a number of 25 women for each study group.…”
Section: Sample Size Calculationmentioning
confidence: 99%